Grafting trimethylaluminum and its halogen derivatives on silica: general trends for 27Al SS-NMR response from first principles calculations. Issue 40 (25th September 2015) - Kerber, Rachel Nathaniel; Kerber, Torsten; Rozanska, Xavier; Delbecq, Françoise; Sautet, Philippe
Abstract : 27 Al solid-state NMR spectrum and parameters for various types of Al monomeric and dimeric alkyl and halogen compounds grafted on silica are interpreted based on the trends obtained from first-principles calculations. Abstract : 27 Al NMR is the method of choice for studying grafted Al species on a large area solid support, such as co-catalysts for α-olefin oligomerization involving mesoporous silica materials. Here, we show how to interpret the 27 Al solid-state NMR spectrum and parameters for various types of Al monomeric and dimeric alkyl and halogen compounds grafted on silica, based on the trends obtained from first-principles calculations. Since most alkylaluminum species tend to form dimers in the gas phase, we chose as prototypes both the AlMe3 monomer and the Al2 Me6 dimer. On top of that the influence of chlorine substituents on the NMR parameters is explored considering all possible isomers. There are two main effects on the Al NMR parameters observed in the case of monomers: (i) the larger π-donating character of the ligands (from Me to Cl for example) leads to a decrease of the quadrupolar coupling constant C Q and (ii) the larger σ-attracting character of the ligand (from Cl to F for example) yields an upfield variation of the Al chemical shift δ ISO while in contrast C Q is increased. The same is true also in the case of dimeric species, with an additional specific effect. By 27 Al solid state NMR we can differentiate clearly between terminal and bridge positions for the substituents. The reason for this phenomenon is explained in terms of different natural localized MO (NLMO) contributions to the C Q parameter. This aspect is important because the surface sites for this type of system are expected to be mostly dinuclear Al species, grafted on the silica surface via either two terminal or two bridging siloxy ligands.